Efecto de láminas de riego y fertilización sobre el rendimiento y rentabilidad del cacao en Calceta, Manabí - Chila Chila, Cristian Fernando (2021)
The aim of the research was to test the effect of irrigation sheets and fertilization plans on the yield and profitability of cocoa in Calceta, Manabi. The research was developed in the polyclone cocoa area at ESPAM-MFL. For the trial it was used a design of complete randomized blocks (DBCA) in factorial arrangement A x B + 2 with eight treatments, three repetitions and 24 experimental units. For this purpose, agronomic, hydric and phytosanitary variables and the net economic benefit were evaluated. Based on the results, it was obtained 2.35 t.ha-1 of dry cocoa under the conventional fertilization plan NPK with 100% Eta/Etm corresponding to the treatment five, allowing reaching a net economic benefit of 2,428.10 USD ha-1 .year-1 . On the other hand, the irrigation sheets of 80% Eta/Etm and 100% Eta/Etm did not show a significant effect on the yield and profitability of the National cocoa. Finally, in the phytosanitary variables of incidence and external severity of moniliasis showed a remarkable effect on the dispersion of the disease in the rainy months and when irrigation was applied.